Sars-Cov-2/Renin-Angiotensin System: Deciphering the Clues for a Couple with Potentially Harmful Effects on Skeletal Muscle - Gonzalez-Rojas, A; Cabello-Verrugio, C; Orozco-Aguilar, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Severe acute respiratory syndrome coronavirus (SARS-CoV-2) has produced significant health emergencies worldwide, resulting in the declaration by the World Health Organization of the coronavirus disease 2019 (COVID-19) pandemic. Acute respiratory syndrome seems to be the most common manifestation of COVID-19. A high proportion of patients require intensive care unit admission and mechanical ventilation (MV) to survive. It has been well established that angiotensin-converting enzyme type 2 (ACE2) is the primary cellular receptor for SARS-CoV-2. ACE2 belongs to the renin-angiotensin system (RAS), composed of several peptides, such as angiotensin II (Ang II) and angiotensin (1-7) (Ang-(1-7)). Both peptides regulate muscle mass and function. It has been described that SARS-CoV-2 infection, by direct and indirect mechanisms, affects a broad range of organ systems. In the skeletal muscle, through unbalanced RAS activity, SARS-CoV-2 could induce severe consequences such as loss of muscle mass, strength, and physical function, which will delay and interfere with the recovery process of patients with COVID-19. This article discusses the relationship between RAS, SARS-CoV-2, skeletal muscle, and the potentially harmful consequences for skeletal muscle in patients currently infected with and recovering from COVID-19. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.